AN IMBEDDING OF FIBONACCI GROUP $F(2,9)$ - Shirvanyan, N. V.; Shirvanyan, V. L. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2006)
In this paper we give imbedding of group Fibonacci F(2,9), given by 9 generators and 9 defining relations in the group $G =< a, b; a^9=1, ab = b^2 a^2 >$.
Keywords: group Fibonacci; defining relations